2007
DOI: 10.1016/j.ab.2007.03.033
|View full text |Cite
|
Sign up to set email alerts
|

A method for in vitro assembly of hepatitis C virus core protein and for screening of inhibitors

Abstract: The assembly of hepatitis C virus (HCV) is not well understood. We investigated HCV nucleocapsid assembly in vitro and the role of electrostatic/hydrophobic interactions in this process. A simple and rapid in vitro assay was developed in which the progress of assembly is monitored by measuring an increase in turbidity, thus allowing the kinetics of assembly to be determined. Assembly is performed using a truncated HCV core (C1-82), containing the minimal assembly domain, purified from E. coli. The increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…These reports highlighted the involvement of numerous amino acids in the production of infectious virus. Other studies, using cell-free and protein expression systems, reported that the N-terminal region of the core protein is important for HCV nucleocapsid assembly (15,25,26) and core protein-RNA interaction (49,57). However, this region of the core protein has not been fully investigated in the context of the HCVcc system.…”
mentioning
confidence: 99%
“…These reports highlighted the involvement of numerous amino acids in the production of infectious virus. Other studies, using cell-free and protein expression systems, reported that the N-terminal region of the core protein is important for HCV nucleocapsid assembly (15,25,26) and core protein-RNA interaction (49,57). However, this region of the core protein has not been fully investigated in the context of the HCVcc system.…”
mentioning
confidence: 99%
“…Fromentin et al (2007) studied a residue 1-82 core construct to follow nucleocapsid formation (Majeau et al, 2004;Fromentin et al, 2007). Based on the discovery of a residue 1-84 self-associating fragment by the yeast twohybrid method applied to a library of fragments of the HCV polyprotein (Flajolet et al, 2000) and the decision to include the residue 82-106 'homotypic' domain that had been reported to be essential for core dimerization Nolandt et al, 1997), we prepared the longer, residue 1-106 N-terminal fragment.…”
Section: Resultsmentioning
confidence: 99%
“…For this report, we chose not to work on nucleocapsid assembly, given the considerable difficulty in selecting the right RNA size and composition, the right core sequence, the reaction conditions and the best method of characterization of the resulting HCV nucleocapsid (Boulant et al, 2005;Fromentin et al, 2007). Instead, we evaluated the influence of the inhibitor peptides on infectious virus production by direct individual addition to cells infected with HCV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations